Conditions Mimicking the Cancer Microenvironment Modulate the Functional Outcome of Human Chorionic Villus Mesenchymal Stem/Stromal Cells in vitro - Basmaeil, Yasser; Al Subayyil, Abdullah; Abumaree, Mohammad; Khatlani, Tanvir (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem/stromal cells isolated from chorionic villi of human term placentae (CV-MSCs) possess unique biological characters. They exhibit self-renewal, directional migration, differentiation, and immunomodulatory effects on other cell lineages, by virtue of which they can be utilized as therapeutic carriers, for drug targeting, and therapy. Tumors display characteristic features of a damaged tissue microenvironment, which is saturated with conditions such as hypoxia, sustained inflammation, and increased oxidative stress. CV-MSCs function normally in a high oxidative stress environment induced by hydrogen peroxide (H2O2) and glucose and also protect endothelial cells from their damaging effects. For their therapeutic applications in a disease like cancer, it is necessary to ascertain the effects of tumor microenvironment on their functional outcome. In this study, we investigated the functional activities, of CV-MSCs in response to conditioned media (CM) obtained from the culture of breast cancer cell line MDA-231 (CM-MDA231). CV-MSCs were exposed to CM-MDA231 for different spatio-temporal conditions, and their biological functions as well as modulation in gene expression were evaluated. Effect of CM-MDA231 on factors responsible for changes in functional outcome were also investigated at the protein levels. CV-MSCs exhibited significant reduction in proliferation but increased adhesion and migration after CM-MDA231 treatment. Interestingly, there was no change in their invasion potential. CM-MDA321 treatment modulated expression of various genes involved in important cellular events including, integration, survival, message delivery and favorable outcome after transplantation. Analysis of pathways related to cell cycle regulation revealed significant changes in the expression of p53, and increased phosphorylation of Retinoblastoma (Rb) and Checkpoint Kinase 2 in CV-MSCs treated with CM-MDA231. To summarize, these data reveal that CV-MSCs retain the ability to survive, adhere, and migrate after sustained treatment with CM-MDA231, a medium that mimics the cancer microenvironment. These properties of CV-MSCs to withstand the inflammatory tumor like microenvironment prove that they may make useful candidate in a stem cell based therapy against cancer. However, further pre-clinical studies are needed to validate their therapeutic usage.